TNF-α contributes to sarcopenia through caspase-8/caspase-3/GSDME-mediated pyroptosis - Jingying Wu; Siming Lin; Weixiao Chen; Guili Lian; Weibin Wu; Ai Chen; Mohammad Ismail Hajary Sagor; Li Luo; Huajun Wang; Liangdi Xie (Cell Death Discovery, 2023)
Abstract Sarcopenia has become a leading cause of disability and mortality in the elderly. It has been reported that programmed cell death (PCD) is associated with the development of sarcopenia that is characterized by reduction of muscle fiber size and number. TNF-α is also validated to play a prominent role in sarcopenia through its complex signaling pathways including cell death signaling. However, it is still unclear whether TNF-α contributes to sarcopenia by mediating pyroptosis, one type of PCD. Here, we first established naturally aged mice with sarcopenia model and confirmed an inflammatory state represented by TNF-α in aged mice. Evidence of GSDME-mediated pyroptosis and activation of apoptotic caspase-8/-3 were also found in skeletal muscle cells of aged mice with sarcopenia. We demonstrated that TNF-α triggered GSDME-mediated pyroptosis in myotubes through activating caspase-8 and caspase-3 by using caspase-8 and caspase-3 inhibitors. Comparing the activation of caspase-8 and GSDME expression between TNF Complex IIa and TNF Complex IIb, TNF-α was found to be more inclined to assemble TNF Complex IIb in activating caspase-8 and triggering pyroptosis. Moreover, pyroptotic myotubes were validated to result in decreased expression of MHC1 and finally loss of myotubes by knockdown of GSDME. Our work reveals a novel mechanism that TNF-ɑ/caspase-8/caspase-3/GSDME signaling-mediated pyroptosis contributes to the development of sarcopenia. Caspase-3/GSDME signaling-mediated pyroptosis may be a promising therapeutic target for sarcopenia.